USE OF INHALATION ANESTHETICS DURING CARDIOPULMONARY BYPASS - E. Yu. Chepurnyak; A. V. Panov; L. S. Lokshin (Вестник анестезиологии и реаниматологии, 2018)
Protection of myocardium from ischemic and reperfusion lesions continues to be an important issue in the modern cardiac surgery. Russian and foreign publications contain a significant number of data about the protective impact of pre- and post-conditioning with inhalation anesthetics (sevoflurane, isoflurane, and desflurane) on the myocardium. The article highlights that this protective action is maximum when these drugs are used during the whole operation and it means during cardiopulmonary bypass as well. Therefore, currently, the listed above inhalation anesthetics are used fairly frequent during cardiopulmonary bypass. However, the technology of inhalation anesthesia during perfusion has a number of specific features: changes in the pharmacokinetics of drugs (which provides impact on the dosing of anesthetics), design of oxygenator, which plays a certain role when the anesthetics are supplied to the blood, monitoring during inhalation anesthesia, technical assistance for this technology and important safety issues. This review describes the above-mentioned aspects.